2020
DOI: 10.3847/2041-8213/ab60a9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ionized Calcium in the Atmosphere of the Ultra-hot Jupiter KELT-9b

Abstract: With a day-side temperature in excess of 4500K, comparable to a mid-K-type star, KELT-9b is the hottest planet known. Its extreme temperature makes KELT-9b a particularly interesting test bed for investigating the nature and diversity of gas giant planets. We observed the transit of KELT-9b at high spectral resolution (R∼94,600) with the CARMENES instrument on the Calar Alto 3.5-m telescope. Using these data, we detect for the first time ionized calcium (Caii triplet) absorption in the atmosphere of KELT-9b; t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 60 publications
1
112
1
Order By: Relevance
“…We note that the planetary disk ignores the wavelength-dependent effect of the planetary radius caused by its atmosphere. As mentioned in Turner et al (2020), the R-M effect is underestimated at the wavelength where the absorption from the planetary atmosphere is strong. To ensure that the model only includes the R-M and CLV effects, for each observation we divided the model by the out-of-transit spectrum after continuum normalisation, and this was subsequently divided out of the data.…”
Section: Data Preparationmentioning
confidence: 84%
See 2 more Smart Citations
“…We note that the planetary disk ignores the wavelength-dependent effect of the planetary radius caused by its atmosphere. As mentioned in Turner et al (2020), the R-M effect is underestimated at the wavelength where the absorption from the planetary atmosphere is strong. To ensure that the model only includes the R-M and CLV effects, for each observation we divided the model by the out-of-transit spectrum after continuum normalisation, and this was subsequently divided out of the data.…”
Section: Data Preparationmentioning
confidence: 84%
“…To avoid this, we chose to use the same number of SYSREM iterations for all orders that maximises the S/N of the detected signal (e.g. De Kok et al 2013;Birkby et al 2017;Turner et al 2020). This method would not result in the true optimised number of SYSREM iterations and might introduce additional noise from the order that has not been 'completely cleaned' by SYSREM as has been pointed out by Alonso-Floriano et al 2019), but it would not affect the result significantly if the S/N of the detection is strong, to begin with.…”
Section: Removal Of Stellar and Telluric Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detections of Fe I, Fe II, Ti II (but not of Ti I; Hoeijmakers et al 2018) are confirming the predicted presence of neutral and ionized species in ultra-hot Jupiters. In Cauley et al (2019); Hoeijmakers et al (2019); Yan et al (2019); Turner et al (2020), more neutral and ionized atomic species are reported, such as Na I, Ca I, Ca II, Mg I, Cr II, Sc II, and Y II. In KELT-9 b, ionized species are more abundant than neutral species, which is A. Wyttenbach et al: Hydrogen Balmer series in KELT-9 b thermosphere Table 2.…”
Section: Parametermentioning
confidence: 99%
“…In addition, as molecules responsible for radiative cooling (e.g., H 2 O) are destroyed by the high dayside temperature (Kitzmann et al 2018;Parmentier et al 2018), refractory elements such as Fe and Mg continue to absorb incident starlight at UV and optical wavelengths and heat the atmosphere at low pressures, inducing a significant dayside temperature inversion (Kitzmann et al 2018;Lothringer et al 2018). Previous observations of KELT-9b have revealed many characteristics that are hallmarks of UHJs, including an extended, escaping atmosphere of dissociated hydrogen (Yan & Henning 2018) and spectral features from ionized Fe, Ti, Mg, Ca, Na, Cr, Sc, and Y in optical transmission spectroscopy (Hoeijmakers et al 2018(Hoeijmakers et al , 2019Yan & Henning 2018;Cauley et al 2019;Turner et al 2020).…”
Section: Introductionmentioning
confidence: 99%